Effects of a Self-Directed Nutrition Intervention Among Adults With Chronic Health Conditions. (February 2018) - Baruth, Meghan; Wilcox, Sara; Jake-Schoffman, Danielle E.; Schlaff, Rebecca A.; Goldufsky, Tatum M.
Chronic diseases are common among adults. A healthy diet may be beneficial for managing the consequences of such conditions. The purpose of this study was to evaluate the effects of a self-directed nutrition program on dietary behaviors among adults with chronic health conditions. As part of a larger trial examining the effects of a self-directed exercise program, participants with arthritis were randomized to a 12-week self-directed exercise or nutrition intervention. Self-reported fruit and vegetable consumption, fat- and fiber-related behaviors were assessed at baseline, 12 weeks, and 9 months. Repeated measures analyses of covariance examined Group × Time changes in dietary behaviors. Effect sizes were computed. Participants ( n = 321) were, on average, 56.5 ± 10.5 years old, had a mean body mass index of 32.9 ± 8.3 kg/m 2, and had 2.0 ± 1.0 chronic health conditions; 88% were female, 65% White, 88% had at least some college education, and 62% married. There were significant Group × Time interactions favoring the nutrition group at 12 weeks for all dietary behaviors ( p < .05) but not at 9 months. Between-group effect sizes were small at 12 weeks and decreased at 9 months. Within-group effect sizes were larger for the nutrition group (small to medium) than the exercise group (none to small) at both time points. A self-directed nutrition intervention can result in meaningful improvements in dietary behaviors among adults with chronic health conditions in the short term.